Hesitation and Repair Strategies in EFL Students’ Academic Presentations: A Case Study - Muhammad Dzimar; Rahma Aulia Usysyfa; Fika Naila Izzati; Faiz Abdillah; Syafhika Rosilatu Zahra; Vadia Fika Munida; Dewi Puspitasari (Fakultas Keguruan dan Ilmu Pendidikan, 2026)
Oral presentations in EFL classrooms require students to communicate ideas fluently while managing the cognitive demands of real-time speech production. However, many learners experience hesitation and frequently repair their utterances, particularly during academic presentations in intercultural communication contexts. This study investigates the use of hesitation and repair strategies in EFL students’ academic presentations in an Intercultural Communication course. Using a qualitative case study design, the study focused on two university students selected purposively due to their frequent use of hesitation during presentations. Data were collected through classroom observations and audio recordings and analyzed using thematic analysis. The findings showed that students commonly used three hesitation types: filled pauses, repetitions, and silent pauses. Regarding repair strategies, self-repair was the most frequently employed, while pair-repair occurred less often. Based on Levelt’s speech production model, filled pauses and silent pauses reflected difficulties in idea generation and speech planning, whereas repetitions indicated problems in lexical retrieval and grammatical formulation. Self-repair demonstrated active speech monitoring, while pair-repair highlighted the supportive role of interaction. The study concludes that hesitation and repair strategies function as important cognitive and communicative mechanisms that help EFL learners manage real-time speech production during academic presentations. These findings provide practical insights for EFL teachers in designing presentation-based learning activities that support students’ speaking fluency, self-monitoring, and strategic communication skills, while also helping students develop greater awareness of hesitation and repair as natural aspects of spoken language production.